The caregiver burden in male romantic partners of women with non-metastatic breast cancer: The protective role of couple satisfaction. (November 2017) - Cairo Notari, Sarah; Favez, Nicolas; Notari, Luca; Charvoz, Linda; Delaloye, Jean-François
We examined the evolution of the subjective burden of romantic partners caring for women with non-metastatic breast cancer and investigated the moderating role of couple satisfaction on caring stress. Forty-seven partners filled out questionnaires 3 and 12 months after surgery. Using a stress process model, we examined caring stressors and moderating factors (couple satisfaction, coping and social support) as predictors of subjective burden. Results showed that subjective burden decreases over time and that the couple satisfaction largely explains it above and beyond other influential variables. Partners dissatisfied with their couple relationship are especially vulnerable to the stress of caregiving.